2021
DOI: 10.3389/frph.2020.561202
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Self-Sampling for Cervical Cancer Screening Among Women Living With HIV and HIV-Negative Women in Limbé, Cameroon

Abstract: Introduction: Like many countries in Sub-Saharan Africa, Cameroon has a high burden of cervical cancer and low availability and uptake of screening. Self-collection has the potential to increase the uptake of cervical cancer screening among Cameroon women. This paper explores patient and community insights surrounding self-collection among women living with HIV and HIV[-] women as well as the barriers and facilitators to obtaining and utilizing self-collected specimens in cervical cancer screening programs.Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 26 publications
(22 reference statements)
2
25
0
Order By: Relevance
“…Some women (23.1%) preferred sampling performed by clinicians, as has been previously reported in other studies [8,[22][23][24]. In Cameroon, an earlier study explored the perceptions and preferences regarding self-versus physician-sampling in a population of women living with HIV and observed that most preferred clinician-sampling [25]. This was found in another study conducted in Britain among Muslim women interviewed in the context of cervical cancer screening [23].…”
Section: Discussionsupporting
confidence: 58%
“…Some women (23.1%) preferred sampling performed by clinicians, as has been previously reported in other studies [8,[22][23][24]. In Cameroon, an earlier study explored the perceptions and preferences regarding self-versus physician-sampling in a population of women living with HIV and observed that most preferred clinician-sampling [25]. This was found in another study conducted in Britain among Muslim women interviewed in the context of cervical cancer screening [23].…”
Section: Discussionsupporting
confidence: 58%
“…Overall, 3178 women were enrolled in those studies and 2105 (66%) of the women were with HIV. Seven studies included women with HIV only, but five studies included both women with HIV and HIV-negative women, with the latter group used as a comparison group [ 36 , 45 , 46 , 47 , 48 ]. Study participants were women between the ages of 25 and 65 years and the sample size for the studies markedly varied.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies were conducted using quantitative methods (six were cross-sectional studies [ 47 , 48 , 49 , 50 , 51 , 52 ], three studies were quasi-experimental studies [ 41 , 45 , 53 ], and one was a prospective observational study [ 36 ]). Two were qualitative studies (interviews [ 46 , 54 ] and focus group discussion [ 46 ]), while one used mixed methods (i.e., focus group and survey [ 53 ]). Most of the cross-sectional studies involved short interventions or instructions where study participants received instructions about screening and/or about steps for using sampling kits [ 36 , 41 , 45 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some women (23.1%) preferred sampling performed by clinicians, as was previously reported in other studies [ 8 , 23 , 24 , 25 ]. In Cameroon, an earlier study explored the perceptions and preferences regarding self- versus physician-sampling in a population of women living with HIV and observed that most preferred clinician-sampling [ 26 ]. This was found in another study conducted in Britain among Muslim women interviewed in the context of cervical cancer screening [ 24 ].…”
Section: Discussionmentioning
confidence: 99%